THERMAL DECOMPOSITION OF WOOD PELLETS BY TGA - Garcia, D. P. [UNESP]; Caraschi, J. C. [UNESP]; Ventorim, G. [UNESP] (Centro Federal Educacao Tecnologica Rio Grande Norte, 2016)
The use of wood pellets for generating thermal energy is spreading in Brazil and thermogravimetric analysis has been widely applied to study the decomposition of wood and its main components such as cellulose, hemicellulose and lignin. The objective of this study was to investigate the thermal behavior of four different samples of wood pellets in non-isothermal conditions by means of thermogravimetric analysis TGA. Assays were performed from room temperature to 500 degrees C with a heating rate of 20 degrees C/min in an inert atmosphere of nitrogen gas with a flow of 100 mL/min. The thermograms showed three decomposition stages: first, assigned to the evaporation of water and volatile materials; the second, refers to the decomposition of the active holocellulose pyrolysis; and third, attributed to the decomposition of lignin pyrolysis passive. Furthermore, it is concluded that most decomposed in the temperature range between 250 degrees C and 400 degrees C, with greater than 60.8 % of the initial mass of the biofuels losses.
Keywords: Wood Pellets; Biomass; Pyrolysis; Thermogravimetric by TGA